Correlation of Intestinal Protozoa Infection with the Nutritional Status of Toddlers Aged 12–59 Months in Jember Regency, East Java, Indonesia - Ardyansyah, Rizky Robeth; Armiyanti, Yunita; Astuti, Ida Srisurani Wiji; Hermansyah, Bagus; Utami, Wiwien Sugih; Sulistyaningsih, Erma (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Intestinal protozoan infection is a problem faced by the global community at all ages. In toddlers, it can cause problems in the form of decreased nutritional status, which is often found in developing countries such as Indonesia. The purpose of this study was to determine the correlation between intestinal protozoa infection and the nutritional status of toddlers.Methods: An observational study with a cross-sectional approach was conducted in October–December 2022 on 45 children aged 12–59 months in Sucopangepok Village, Jelbuk District, Jember Regency, East Java, Indonesia using, consecutive sampling techniques and a total sample size. Nutritional Status was measured based on body weight to body length using the WHO Anthropometric Calculator. Stool examination used the direct smear method and modified Ziehl-Neelsen staining. Data was analyzed using the Cramer's V test. The p-value less than 0.05 was considered statistically significant.. Results: The incidence of wasted children was 15.6% and severely wasted was 2.2%. Intestinal protozoan infection had an incidence of 15.6%. The species detected were Giardia lamblia (6.7%), Cryptosporidium parvum (6.7%), and Blastocystis hominis (2.2%). Statistical analysis showed there was no correlation between intestinal protozoan infection and nutritional status (p= 0.441; r = 0.191).Conclusions: There is no correlation between intestinal protozoan infection and the nutritional status of toddlers. However, comprehensive collaboration between the government and the community needs to be improved, as well as healthy lifestyles for toddlers which also need to be encouraged to overcome nutritional problems in children under five old and prevent intestinal protozoa infections.